The effects of nitrogen pollutants on the isotopic signal (δ15N) of Ulva lactuca: Microcosm experiments. (15th February 2017) - Orlandi, Lucia; Calizza, Edoardo; Careddu, Giulio; Carlino, Pasquale; Costantini, Maria Letizia; Rossi, Loreto
Abstract: Effects of two chemical forms of Nitrogen (NH4 + and NO3 − ) on δ 15 N in Ulva lactuca were analysed separately and in mixture at two concentrations. We assessed whether the δ 15 N values of U. lactuca discriminate between Nitrogen from synthetic fertilisers (inorganic) and from fresh cow manure (organic), and the isotopic ability of the macroalga to reflect Nitrogen concentrations. Isotopic signature and N content of the macroalga reflected different nitrogenous sources and their concentrations after 48 h. The inorganic Nitrogen source (NH4 NO3 ) altered the isotopic values of the macroalgae more than Nitrogen from fresh cow manure (NO3 − ). δ 15 N values observed in the mixed solution did not differ from those displayed in NH4 NO3 treatment alone. We conclude that stable isotope analysis of U. lactuca collected in an unpolluted site and experimentally submerged in sites suspected of being affected by disturbance is a useful tool for rapid monitoring of anthropogenic discharges of Nitrogen pollutants. Highlights: The δ 15 N values of Ulva lactuca exposed to various nitrogen pollutants were assessed. Ulva responded to NH4 + but not to NO3 − inputs if derived from fresh cow manure. Ulva δ 15 N values depended more on inorganic than organic N sources in mixtures. The isotopic variation of U. lactuca was sensitive to total N concentration. Short-term exposure was enough for isotopic signals to approach equilibrium.